The effects of preoperative blood pressure on early failure rate of distal arteriovenous fistulas for hemodialysis access. Issue 3 (2nd May 2019) - Pandey, Siddharth; Kumar, Manoj; Agrawal, Manav; Singh, Manmeet; Aggarwal, Ajay; Garg, Gaurav; Agarwal, Samarth; Sankhwar, Satyanarayan
Abstract: Introduction: The first choice of vascular access for hemodialysis in patients with end‐stage renal disease is a distal radiocephalic arteriovenous fistula (AVF). Early failure rates for these AVFs vary from 10% to 53%. The effects of predialysis hypotension on failure of AVFs have been described in the literature. Weather lower blood pressures affect early AVF failure has not been extensively studied. We conducted this study to evaluate the effects of preoperative blood pressures on early AVF failure. Methods: Ours was a prospective observational study over a period of 2 years that included 224 patients who underwent distal radiocephalic AVF creation. Only those patients were included whose fistulas were made by surgeons with an experience of greater than five cases. The systolic, diastolic, and mean arterial pressures (MAPs) were recorded preoperatively. Early failure was defined as failure to achieve vascular access from the fistula within first 4 months of its creation. Findings: The overall early failure rate was 27.7%. Early failure was more common in females and diabetic patients. The systolic, diastolic, and MAPs were significantly lower in patients with early failure (P < 0.05). In a multivariable adjusted analysis, lower preoperative diastolic and MAPs were predictors for early failure of distal radiocephalic AVF. Discussion: Our study shows that patients with early failure of AVFs have lower preoperative blood pressure. A larger study is required to substantiate our findings and define target preoperative blood pressure for AVF creation.